Playing MUSIC — building context‐aware and self‐adaptive mobile applications. (17th April 2012) - Floch, J.; Frà, C.; Fricke, R.; Geihs, K.; Wagner, M.; Lorenzo, J.; Soladana, E.; Mehlhase, S.; Paspallis, N.; Rahnama, H.; Ruiz, P.A.; Scholz, U.
SUMMARY Although the idea of context‐awareness was introduced almost two decades ago, few mobile software applications are available today that can sense and adapt to their run‐time environment. The development of context‐aware and self‐adaptive applications is complex and few developers have experience in this area. On the basis of several demonstrators built by the joint European research project MUSIC, this paper describes typical context and adaptation features relevant for the development of context‐aware and self‐adaptive mobile applications. We explain how the demonstrators were realised using the open‐source platform MUSIC and present the feedback of the developers of these demonstrators. The main contribution of this paper is to show how the development complexity of context‐aware and self‐adaptive mobile applications can be mastered by using an adaptation framework such as MUSIC. Copyright © 2012 John Wiley & Sons, Ltd.